PENGARUH PENERAPAN MODEL PEMBELAJARAN TEAM - ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN MEDIA FLIPBOOK TERHADAP KETERAMPILAN BERPIKIR ANALITIS DAN KETERAMPILAN KERJASAMA SISWA - Agustina Simorangkir; M. Raidil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to evaluate the impact of the Team-Assisted Individualization (TAI) learning model, supported by flipbook media, on students' analytical thinking and teamwork skills regarding chemical equilibrium. Analytical thinking skills were measured through a post-test, while teamwork skills were assessed through observation sheets completed by observers. The study employed a quasi-experimental design with a post-test only control group, involving a total population of 250 students from grades 11 Science 1 to science 5. Two classes were selected as samples, with each group (experimental and control) consisting of 34 students. Data collected were analyzed using the Manova test to examine the effect of the TAI model with flipbook media on students' analytical thinking and teamwork skills in the chemical equilibrium topic. The results yielded a p-value of 2.2 x 10-16, This demonstrates a notable difference in both analytical thinking and teamwork skills between the experimental and control groups. The univariate test results for each variable further confirmed the effect of the TAI model with flipbook media on students' analytical thinking and teamwork abilities.